The enemy within: criminal law and ideology in interwar Romania - Cercel, Cosmin Sebastian (Hart Publishing, 2015)
The aim of this chapter is to offer a critical analysis of the uses of criminal law in the context of the royal dictatorship and the rise of fascism in Romania during the 1930s. It explores the effacement of traditional categories of legality entailed by the emergence of the Criminal Code of 1936, by focusing on the notion of crimes against the constitutional order and its intricate relation to the socio-political context of the time. In this sense this chapter investigates critically and historically the relation between criminal law, constitutional law and the rise of fascism in Romania while stressing three crucial and overlooked elements: the ideological tenets of the Code present both in its substantial and formal structure, the politico-legal significance of the Code in the historical moment of its enactment, and the erosion of classical forms of legality determined by the Code’s ideological appropriation. Moreover, it tackles the question of continuity between democratic legislation and authoritarian law.